CO2 Fluid Flow Patterns near Major Deep Faults: Geochemical and 3D Seismic Data from the Ying-Qiong Basin of the South China Sea. (11th March 2022) - Yu, Junfeng; Song, Ruiyou; Pei, Jianxiang; Wu, Qilin; Shao, Yuan
Abstract : CO2 and hydrocarbon fluids typically migrate from deeper layers into the shallow crust via large deep faults. Consequently, CO2, hydrocarbon, and water reservoirs tend to occur in traps near deep and large faults. In this study, we use structural and stratigraphic data to identify and predict CO2 and hydrocarbon gas reservoirs near major deep faults. In order to investigate how CO2 accumulates in the major deep faults of the Ying-Qiong Basin (YQB), we quantify the carbon footprint of this area by analyzing the No. 1 fault, the No. 2 fault, and the adjacent gas reservoirs. Using 3D seismic data and geochemical data, we determine how the fault structure affects the ambient CO2 enrichment on a given fault. Our results indicate that the LD10 and BD19 gas reservoirs have high inorganic CO2 contents, while the HK29 gas reservoir has a low organic CO2 content. Based on our analyses, we conclude that the gas source, fault activity, and fault structure control the CO2 accumulation in subsurface layers. While mantle-derived volcanic inorganic CO2 disperses upward along the main fault when a given fault is independent (i.e., it lacks secondary faults), the absence of additional vertical migration channels largely prevents the CO2 from travelling upward through thick mudstone cap rocks and collecting in shallow traps. These shallow traps are typically filled by shallow organic CO2 sources. However, parallel forward fault-step structures, such as secondary faults, can transport gas that is produced at deeper sources (such as CO2 generated by basement limestone) to shallower depths. If the hanging wall of a deep fault has many branching secondary faults, then these intersecting faults act as conduits that enable mantle-derived CO2 to travel vertically into shallow layers.